2011
DOI: 10.2174/1874088x01105010178
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Mechanical Characteristics and Tribological Mechanisms of Nanometric Zirconia Dental Ceramics

Abstract: This study was focused on the experimental investigations about mechanical characteristics and tribological mechanisms of nanometric zirconia dental ceramics. A universal mechanical testing machine was used to test the threepoint flexural strength and the fracture toughness. A microhardness tester was used to test the Vickers hardness of the test specimens. An MRH-3 digital-display high-speed ring-on-block tribometer was used for frictional wear experiments. A PGI800 coarseness profiling instrument was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The convection current and radiation on the surface in touch with the air are ignored and only the heat conduction on the contact surface between the molten drop and matrix and the heat conduction in the molten drop and matrix respectively are considered [16][17][18][19].…”
Section: Thermal Transmission Modelmentioning
confidence: 99%
“…The convection current and radiation on the surface in touch with the air are ignored and only the heat conduction on the contact surface between the molten drop and matrix and the heat conduction in the molten drop and matrix respectively are considered [16][17][18][19].…”
Section: Thermal Transmission Modelmentioning
confidence: 99%
“…The development of industrial technologies has led to the extensive use of ceramic materials with high strength, high hardness, high chemical stability, low thermal expansion coefficient, and abrasion resistance in the fields of machinery, metallurgy, chemical industry, energy, and bio-engineering (Li et al, 2011c). The reason is the special physical and chemical properties of these ceramic materials that make them difficult to process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they measured the grinding force, surface roughness, the temperature of the grinding zone, and grinding ratio. Results showed that the cooling effect of the water droplets processing liquid attached by minimum quantity oil film as inferior to traditional processing liquid such as emulsion solution and soluble concentrates, yet presenting sound lubricating property [20][21][22][23]. It also presented excellent advantages in regard of processing precision and the grinding wheel life.…”
Section: Introductionmentioning
confidence: 99%